The Life of Mammals - Attenborough D. David (London, BBC, 2002)
Of marsupials, mice and men. Evolution, and Sir David Attenborough's 23-year sequence of books and BBC television 'Life' films, have culminated in the mammals and the explosion of awareness and intelligence. In the very short period of 100 million years - a mere blink in evolutionary time — the first mammals have arrived at world dominance. This came largely from hair and milk. Insulation and central heating made them adaptable to any surroundings. Care of the young led to learning and bigger brains. Otters, camels, lions, foxes and sheep, moles undergound, whales at sea, bats in the air, polar bears, antelope, squirrels, mice, monkeys and man have exploited every habitat and every food source — the basis of this new narrative.